Aminoacetonitrile as precursor for nitrogen rich stable and insensitive asymmetric N-methylene-C linked tetrazole-based energetic compounds. Issue 32 (27th July 2017) - Kumar, Dheeraj; Imler, Gregory H.; Parrish, Damon A.; Shreeve, Jean'ne M.
Abstract : This work demonstrates the synthesis and characterization of nitrogen rich stable and insensitive N -methylene-C Linked tetrazole-based energetic compounds. Abstract : Reaction of aminoacetonitrile with cyanogen azide resulted in acetonitrile derivative of amino(tetrazole), 1, which on further reaction with sodium azide in the presence of ammonium chloride resulted in compound2 with N -methylene-C bridged tetrazole and amino-tetrazole moieties. Reaction of2 with 100% nitric acid resulted in N -(1-((1 H -tetrazol-5-yl)methyl)-1 H -tetrazol-5(4 H )-ylidene)nitramide (4 ) having N -methylene-C bridged nitroimino-tetrazole and tetrazole moieties. Various energetic salts based on these three types of tetrazole derivatives (tetrazole, amino-tetrazole and nitroimino-tetrazole) in2 and4 were obtained. All the compounds were thoroughly characterized by IR, NMR [ 1 H, 13 C{ 1 H}, 15 N], elemental analysis, and differential scanning calorimetry (DSC). Some of them were also structurally characterized with single-crystal X-ray diffraction studies. Heats of formation and detonation performances for all the energetic compounds were calculated using Gaussian 03 and EXPLO5 v6.01 programs, respectively.